2021
DOI: 10.2320/matertrans.mt-m2020166
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ferromagnetic τ-Mn–Al–C by Reactive Sintering

Abstract: Ferromagnetic MnAlC (¸-phase) can be synthesized by a single-route conventional reactive sintering method. The maximum magnetization and coercivity were 75.8 Am 2 /kg and 57 mT, respectively. The¸-phase fraction was evaluated to be 81 mass% for Mn 55 Al 45 C 2 annealed at 1273 K. The¸-phase of Mn 55 Al 45 C 2 can be synthesized at an annealing temperature from 873 to 1273 K, whereas that of Mn 55 Al 45 cannot be synthesized. It was indicated that the phase stability of the hcp-phase (¾-phase) was improved by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Texturing along [001] axes of τ-MnAl phase was observed, and coercivity was found to be at around 2500 Oe even after 15 h milling. In a very recent publication, R. Kobayashi et al [45] have shown that ferromagnetic Mn-Al-C (τ-phase) can be synthesized by a single-route conventional reactive sintering method. The maximum magnetization and coercivity were 75.8 Am 2 /kg and 57 mT, respectively, when τ-phase fraction was about 81 mass% for Mn 55 Al 45 C 2 annealed at 1273 K. The results have been interpreted in terms of phase stabilization by carbon addition during ε-τ transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Texturing along [001] axes of τ-MnAl phase was observed, and coercivity was found to be at around 2500 Oe even after 15 h milling. In a very recent publication, R. Kobayashi et al [45] have shown that ferromagnetic Mn-Al-C (τ-phase) can be synthesized by a single-route conventional reactive sintering method. The maximum magnetization and coercivity were 75.8 Am 2 /kg and 57 mT, respectively, when τ-phase fraction was about 81 mass% for Mn 55 Al 45 C 2 annealed at 1273 K. The results have been interpreted in terms of phase stabilization by carbon addition during ε-τ transformation.…”
Section: Introductionmentioning
confidence: 99%